REDUCING LABORATORY TESTING IN A TERTIARY MEDICAL CENTRE: A RESIDENT-LED MULTILEVEL QUALITY INTERVENTION. Issue 11 (22nd October 2015) - Lee, Matilda Xw; Choong, Clarice; Teo, Winnie ZY; Fan, Kristie HR; Lim, Lye Heng; Ong, Lizhen; Saw, Sharon; Lim, Tow-Keang; Santosa, Amelia; Lahiri, Manjari
Abstract : Background: Hospital in-patient laboratory testing is steadily rising, contributing to increasing healthcare costs, errors, and unnecessary treatments. Strategies to reduce over-utilization of laboratory tests have been tried with mixed results. Objectives: To reduce the volume of the most frequently ordered laboratory tests by 10% over 6 months. Methods: The most commonly ordered tests in medical wards were determined and a survey was conducted among residents and faculty to determine the perceived causes of over-testing. A resident-led multilevel collaborative campaign was launched. This comprised of education sessions (intern and resident teaching), cost awareness information (mini cards, computer screensavers), publicity (reminders to on-call teams), regular audits and feedback. The focus was on changing test ordering behavior and culture. Monthly average test numbers were compared with those in the preceding year. Results: The campaign was launched in 8 medical wards from the period of September 2014 to February 2015. The top 6 laboratory tests/panels (full blood count, renal panel, calcium panel, liver panel, C-reactive protein and acute coronary screen) were selected based on order-volume. There was a 9.4% reduction in tests ordered during the study period, resulting in costs savings estimated at $34, 235 per month. Results were sustained over the 6-month study period. Reduced testing had no effect on in-hospital mortality (3.17% post-intervention vs. 3.02% pre-intervention, p=0.47). Conclusions: The development of a multilevel collaborative initiative resulted in reduction in test-ordering and significant and sustained costs savings. Approaches targeting culture change may be a feasible method of maintaining a lean health care system.Figure 1 Figure 2 Figure 3